MATHEMATICAL MODELING OF DRYING CORN GRAINS FOR CONDITIONS OF THE “BRAZILIAN CERRADO” - CORADI, PAULO CARTERI; MILANE, LÉLIA VANESSA; DIAS, CHARLES FABIAN; BAIO, FÁBIO HENRIQUE ROJO (REVISTA BRASILEIRA DE MILHO E SORGO, 2016)
The need to maintain the quality of the corn kernels during drying becomes of great importance the knowledge of the phenomena that occur at this stage. The objective of this study was to model the drying of grains in different air temperature conditions used in dryers in the Brazilian cerrado region. Drying was carried out with three drying temperatures (80, 100 and 120 0C) in an oven with forced air circulation and convection. To adjust the mathematical models to experimental data, there were non-linear regression analysis using software Statistica 7.0®. It was observed that the higher the temperature of the drying air (120 °C) the faster the product has reached the equilibrium moisture content. It was found that the model was Midilli to define the best corn drying curves at air temperatures of 80, 100 and 120 °C. The effective diffusivity obtained from the drying of corn was higher (5.4 x 10-13 m2 s-1) at a temperature of 120 °C. In conclusion, the drying of the grain at higher temperatures (above 100 °C), so has the power isosteric desorption (3885 kJ kg-1) to carry out the process.